Trust in industrial human–robot collaboration - Charalambous, George; Fletcher, Sarah R. (Springer, 2021)
Trust has been identified as a key element for the successful cooperation between humans and robots. However, little research has been directed at understanding trust development in industrial human-robot collaboration (HRC). With industrial robots becoming increasingly integrated into production lines as a means for enhancing productivity and quality, it will not be long before close proximity industrial HRC becomes a viable concept. Since trust is a multidimensional construct and heavily dependent on the context, it is vital to understand how trust develops when shop floor workers interact with industrial robots. This chapter provides a literature review of how trust can vary between human-robot collaboration and generic human-automation interaction whilst providing recent empirical findings on the topic of trust in industrial HRC carried out at Cranfield University.